Competencia de los sistemas de cultivos asociados de maiz-frijol - Laing, Douglas R. (International Center for Tropical Agriculture, 1978)
Results obtained in expt at CIAT are analyzed 20 maize hybrids were planted in 4 replications for 2 seasons, in monoculture and in association with bean genotypes P566 and P589, types II and IV (bush and climbing). In monoculture, Tropical White Mix gave the more than yield in both seasons (7.26 and 8.08 t/ha). A significant decrease was observed in maize yield for the majority of the varieties associated with type IV beans in both seasons, the lst season, the yield of the majority of the maize samples decreased when associated with Type II beans, whereas in the 2nd season there were significant increases. The net profit/ha was determined taking into account yield, current market prices and production costs; it is concluded that the maize/bean association is more profitable than monoculture. A negative correlation was found in both seasons (-0.89 and -0.70) between the yields of associated maize/beans (Type II); consequently, yields of a high-yielding maize var. associated with beans (Type II) tends to decrease. A short maize var (ICA-H210) and a Type IV bean (P589) were planted; compared to monocultures, great decreases in yields (44.5 and 50,5 percent for maize and beans, resp.) were observed. (CIAT)